The influence of ownership on performance: An empirical study - Oswald, Sharon L.; Jahera, John S. (Strategic Management Journal, 1991)
Abstract This research examines the relationship between ownership structure and financial performance in the context of the agency theory. It improves upon previous research by presenting an improved risk‐adjusted performance measure, by using a larger sample size than prior work and also by controlling for firm size differences. The results suggest that ownership is significantly related to firm financial performance even after controlling for size.